Live bird markets as evolutionary epicentres of H9N2 low pathogenicity avian influenza viruses in Korea - Sung-su Youk; Dong-Hun Lee; Jei-Hyun Jeong; Mary J. Pantin-Jackwood; Chang-seon Song; David E. Swayne (Emerging Microbes and Infections)
Live bird markets (LBMs) in Korea have been recognized as a reservoir, amplifier, and source of avian influenza viruses (AIVs); however, little was known about the role of LBMs in the epidemiology of AIVs in Korea until recently. Through 10 years of surveillance (2006–2016) we have isolated and sequenced H9N2 viruses in Korean LBMs. To understand how H9N2 evolves and spreads in Korea, a statistical Bayesian phylogenetic model was used. Phylogenetic analysis suggests that three separate introductions of progenitor gene pools, Korean domestic duck-origin and two wild aquatic bird-origin AIVs, contributed to the generation of the five genotypes of H9N2 viruses in Korea. Phylogenetic reconstruction of ecological states infer that the LBMs are where chickens become infected with the virus, with domestic ducks playing a major role in the transmission and evolution of the H9N2 viruses. Three increases in the genetic diversity of H9N2 viruses were observed and coincided with transitions in host species and the locations (domestic farm, LBM, slaughterhouse, and wild aquatic bird habitat) where the viruses were isolated, accompanying genetic reassortment. Following the introduction of a wild aquatic bird-origin AIVs in 2008, six genes of the Korean lineage H9N2 virus were replaced with genes originating from wild aquatic birds, and viruses with this new genotype became predominant in Korean LBMs.